HUBUNGAN PEMANFAATAN DANA BANTAUAN OPERASIONAL KESEHATAN DENGAN CAKUPAN PROGRAM KESEHATAN IBU DI KABUPATEN KONAWE SELATAN: The Relationship Between The Utilization of Health Operational Assistance Funds and The Coverage of Maternal Health Programs in South Konawe Regency - Sunarsih; Sija Tiku; Timbul Supodo (LPPM - STIKES Pemkab Jombang, 2020)
Introduction: Health Operational Assistance (HOA) is the government program for financing the mandatory health effort which is include promotive and preventive health effort. However untill now the health programs that funded by BOK (HOA) especially maternal health program is not indicate the maksimum result or it is not achieve the target of Minimum Service Standdard that required to achieve the 100% targets. Every year the maternal mortality is excelsior, the coverage maternal health is decline. Objective: This research is aimed to find out the relationship between the utilization of health opperational assistance funds and the coverage of the maternal health program namely the fourth antenatal health service (K4), Childbirth assistance by the health and childbirth labour in health facility in South Konawe regency based on HOA (BOK) fund allocations aspect and the implementation of mini clinic workshop. Method: The kind of research is cross sectional study. Population in this research are the head of clinic, the HOA (BOK) fund’s organizer, the maternal health program’s organizer, coordinator midwife, the village’s midwife in 23 clinics in South Konawe regency. The population number in this research are 115 respondents. Sample in this research are 85 respondents from 17 clinics. Sample interpretation techniques in this research used Stratified Proportional Simple Random Sampling. Analysis data based on descriptive and inferential held with bivariate analysis by meas of chi square stage. Result: Majority the respondent’s age around 26-30, educational level on stratum Diploma III. The research result indicates that there is no relationship between mini clinic workshop and coverage maternal health program, acquired value X2 arithmetic< X2 table (0,360<3,841). Existing meaningful relation between BOK (HOA) fund’s allocation and coverage maternal health program, value X2 arithmetic < X2 table (4,663 > 3,841). The result of closeness relation test indicates coefficient Phi(?) as big as 0,427, this case indicates the strength relation between BOK (HOA) fund’s allocation and coverage maternal health program in South Konawe regency. Conclusion: interm rise the coverage maternal health program, the evaluatio of BOK (HOA) fund’s utilizing is necessary in clinic especially on fund’s allocation distribution for priority and evaluation of mini clinic workshop implementation. Keywords :BOK (HOA) fund allocations, Coverage maternal health program, Mini clinic workshop.